Analisis Peranan Konsultan Pajak Terhadap Kepatuhan Wajib Pajak Dalam Memenuhi Kewajiban Perpajakan - Dian Khairannisa; Charoline Cheisviyanny (Universitas Negeri Padang, 2019)
This study aims to determine whether there is a role for tax consultants on taxpayer compliance in fulfilling tax obligations. This research is a type of qualitative research. Data collection techniques are semi-structured interviews and triangulation. Interviews were conducted with companies in the city of Padang. The population in this study were companies in the city of Padang, and 20 companies were sampled in this study. The result of this study prove that (1) the reasons for taxpayers using tax consultant services are divided into three, namely lack of knowledge of taxpayers regarding all tax regulations, complicated taxation systems and the last reason is that tax obligations can be carried out effectively and efficiently, (2) the type of tax consultant that is chosen by many corporate taxpayers is type honest consultant because taxpayers use tax consultants rather than aiming to help find loopholes but to help taxpayers who have difficulty managing their own taxes, and (3) advice from tax consultants chosen by all taxpayers are conservative advice, because companies do not want to bear the risk of using aggressive sanctions. For the next researcher, I suggest collecting data not only from interviews, but also suggested for further research to conduct research into a wider scope in various regions and add other variables related to the role of tax consultants for taxpayers in Indonesia